Mort Rainey’s Split Personality in Secret Window - Cynthya Sandjaya; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2013)
Psychological issue is the main issue discussed in David Koepp’s Secret Window through its main character, Mort Rainey. Rainey’s psychological struggle will be the main theme in this research. This thesis examines Rainey’s split personality. Furthermore, in this study, we want to analyze the process of how Mort Rainey’s personality splits into two different personalities. To meet the answer of this study, we will use the theory of Dissociative Identity Disorder with a support from Sigmund Freud’s psychoanalytic theory about the three psyche agents. In this study, we discover that the process of Mort Rainey’s split personality begins with a traumatic experience, then continues with the repression and compartmentalization to create John Shooter. Finally, the split personality that Mort Rainey experiences is useful as a great defense for Mort Rainey to cope with his trauma.